2016
DOI: 10.1111/jace.14600
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants of polycrystalline Ti3AlC2 and Ti3SiC2 measured using coherent inelastic neutron scattering

Abstract: The magnitude of the single‐crystal elastic constant c44 in the MAX phase Ti3SiC2 is under debate. In this paper, estimates for the magnitude of c44 for MAX phases Ti3AlC2 and Ti3SiC2 are determined from a partially oriented polycrystalline sample via coherent inelastic neutron scattering. The largely quasi‐isotropic nature of these Mn+1AXn phase elastic constants as previously predicted by density functional theory calculations is confirmed experimentally for Ti3AlC2 to be c44=115.3 ± 30.7 GPa. In contrast, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…The calculated values for the bulk modulus of Ti 3 SiC 2 and Ti 3 AlC 2 are 139 GPa and 182 GPa respectively. These values agree well with the reported value by Gray et al 47 , with less than 13% and 7% deviation respectively for Ti 3 AlC 2 and Ti 3 SiC 2 . Moreover, our results for Shear modulus of 87 GPa for Ti 3 AlC 2 although are lower than the reported experimental value in Table 3, the results of Ti 3 SiC 2 of 121 GPa are in good agreement with the reported value.…”
Section: And Voigt Bulk Modulus (B V ) Reuss Bulk Modulus (B R ) Bysupporting
confidence: 93%
“…The calculated values for the bulk modulus of Ti 3 SiC 2 and Ti 3 AlC 2 are 139 GPa and 182 GPa respectively. These values agree well with the reported value by Gray et al 47 , with less than 13% and 7% deviation respectively for Ti 3 AlC 2 and Ti 3 SiC 2 . Moreover, our results for Shear modulus of 87 GPa for Ti 3 AlC 2 although are lower than the reported experimental value in Table 3, the results of Ti 3 SiC 2 of 121 GPa are in good agreement with the reported value.…”
Section: And Voigt Bulk Modulus (B V ) Reuss Bulk Modulus (B R ) Bysupporting
confidence: 93%
“…These values agree well with the reported value by 32 , with less than 13% and 7% deviation respectively for Ti3AlC2 and Ti3SiC2. Moreover, our results for shear modulus of 87 GPa for Ti3AlC2 although are lower than the reported experimental value in Table 3, the results of Ti3SiC2 of 121 GPa are in good agreement with the reported value.…”
Section: Elastic Propertiessupporting
confidence: 92%
“…It was observed that, for both Ti 3 AlC 2 and Ti 3 AlBC compounds, C 11 is greater than C 33 , which is in line with research findings. 25 The bulk modulus ( B ), shear modulus ( G ), Young's modulus ( Y = 9 BG /(3 B + G )), 26 and Poisson's ratio of Ti 3 AlBC were calculated. The bulk modulus of Ti 3 AlBC was estimated to be 139 GPa.…”
mentioning
confidence: 99%